Technology Enable Language Learning: Mediating Role of Collaborative Learning - Ratna Rintaningrum; Kartika Nuswantara; Arfan Fahmi; Umi Trisyanti; Siti Zahrok (Yayasan Adra Karima Hubbi, 2024)
In the current technological era, language learning has experienced significant changes. The implementation of technology in language learning has enabled the development of innovative learning methods, especially in the context of collaborative learning. Optimizing language and technology skills can be a provision to face the demands of life which are always changing according to the times. Therefore, students need to explore technology in the learning process. This research aims to investigate the role of technology in mediating collaborative learning in the context of language learning. Combining language learning with technology is a relevant solution to mediate collaborative learning. An approach that involves a reciprocal relationship between educators and students to achieve maximum learning goals. The method used in this research is quantitative. The steps are to create a statement related to technologically enabled language learning that can mediate the role of collaborative learning. Then it is formulated into a Google form and filled in by students. Then the data is collected input and processed using the SPSS application. The correctness of the data can be proven by statements made on the Google form which are adjusted to the facts that occur in the world of education. The results of this research state that in language learning, technology plays a very important role in becoming an intermediary for optimizing collaborative learning. Creating a new innovative educational perspective that is increasingly sophisticated, helping students develop more complex and in-depth thinking abilities so that they can provide effective solutions related to all forms of challenges that occur in the world of education. This research concludes that teachers are advised to better understand language learning through technology so they can teach students how to adapt to increasing technological changes. So that it can expand opportunities for creativity in learning and enrich the learning experience through the skills practiced by the teacher.